The circular economy approach in a flexible housing project: A proposal for affordable housing solution in Malaysia - Mohd, Zairul; Wamelink, J.W.F (Hans); Gruis, .H.; Heintz, J.L.; Mat, Nasir, Nasyairi (International Journal of Engineering and Technology, 2018)
The demand for housing and affordable housing specifically will always become challenges for the government of the day. The solutions at the moment between conventional construction and IBS facing quality and costing problems respectively. In this article, it proposes the introduction of circular economy in a flexible housing project. To support the industrial revolution 4.0, this study is suggesting an alternative approach towards manufacturing the house as a commodity for the users. The idea of a circular economy is to reduce the price consumption by extending the lifespan of the housing unit. Towards the end, this article reports a design workshop conducted with the architects to produce a proof-of-concept of an affordable flexible house using CE (circular economy) principles. The flexible affordable house offers a solution to the lack of affordable housing and proposes alternative solutions to the problems. The study will benefit the government and Malaysians who opt for alternative housing in the future.